2012
DOI: 10.1039/c2dt30314k
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated linkage isomerism in single crystals of nickel, palladium and platinum di-nitro complexes – a photocrystallographic investigation

Abstract: Low temperature, single crystal photocrystallographic studies have been carried out on four square planar Group 10 complexes [Ni(PEt(3))(2)(NO(2))(2)] 1, [Pd(PPh(3))(2)(NO(2))(2)] 2, [Pd(AsPh(3))(2)(NO(2))(2)] 3 and [Pt(PPh(3))(2)(NO(2))(2)] 4, in which the two nitro groups adopt the trans configuration. Irradiation with UV light, at 100 K, of single crystals of complexes 1-3 photoisomerise from the η(1)-NO(2) nitro form to the η(1)-ONO nitrito form occurred. Complex 1 underwent 25% conversion to the nitrito f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…There is precedent for slower reaction kinetics in photoactive linkage isomer crystals with heavier transition metals (TMs), 29 and this has generally been linked to the expectation of lower kinetic lability for ligands attached to heavier TMs. 30 Secondly, though high photo-activation is achieved in both 1 and 2 at 150 and 200 K respectively, despite structural similarities 100% conversion is only reached in the Pd-system 1.…”
Section: Comparison Of Photo-isomerisation Behaviour In 1 Andmentioning
confidence: 99%
“…There is precedent for slower reaction kinetics in photoactive linkage isomer crystals with heavier transition metals (TMs), 29 and this has generally been linked to the expectation of lower kinetic lability for ligands attached to heavier TMs. 30 Secondly, though high photo-activation is achieved in both 1 and 2 at 150 and 200 K respectively, despite structural similarities 100% conversion is only reached in the Pd-system 1.…”
Section: Comparison Of Photo-isomerisation Behaviour In 1 Andmentioning
confidence: 99%
“…Nitro-nitrito isomerism has also been reported in systems containing different transition-metal centres, including palladium (Bajwa et al, 2012) and platinum species (Warren et al, 2012). In the latter photocrystallographic study, the absorption properties of the sample are shown to be affected by the nature of the metal centre.…”
Section: Thermal Nitro-nitrito Isomerizationmentioning
confidence: 89%
“…The conversion rate varied from 16% for endo-Ni(aep)(ONO) 2 after exposure to 470 nm light, to 46% for endo-Pd(PPh 3 ) 2 (ONO) 2 after exposure to 362 nm light (up from 30% using 400 nm light). In addition to displaying lower nitrite to nitrito conversion, the nitrito anions in Ni(aepy)(ONO) 2 Partial conversions could be obtained by illumination of Ni(aep)(NO2)2, Ni(aepy)(NO2)2 (aep = 1-(2-aminoethyl)piperidine, aepy = 1-(2-aminoethyl)pyrrolidine) [55], Pd(PPh3)2(NO2)2 and Pd(AsPh3)2(NO2)2 [56] (Figure 6). The conversion rate varied from 16% for endo-Ni(aep)(ONO)2 after exposure to 470 nm light, to 46% for endo-Pd(PPh3)2(ONO)2 after exposure to 362 nm light (up from 30% using 400 nm light).…”
Section: Photocrystallographymentioning
confidence: 99%
“…Partial conversions could be obtained by illumination of Ni(aep)(NO 2 ) 2 , Ni(aepy)(NO 2 ) 2 (aep = 1-(2-aminoethyl)piperidine, aepy = 1-(2-aminoethyl)pyrrolidine) [55], Pd(PPh 3 ) 2 (NO 2 ) 2 and Pd(AsPh 3 ) 2 (NO 2 ) 2 [56] (Figure 6). The conversion rate varied from 16% for endo-Ni(aep)(ONO) 2 after exposure to 470 nm light, to 46% for endo-Pd(PPh 3 ) 2 (ONO) 2 after exposure to 362 nm light (up from 30% using 400 nm light).…”
Section: Photocrystallographymentioning
confidence: 99%
See 1 more Smart Citation